Numerical Investigation of Heat Transfer Enhancement in a Circular Tube with Rectangular Opened Rings - Arkan Altaie; Moayed R. Hasan; Farhan Lafta Rashid (Institute of Advanced Engineering and Science, 2015)
Turbulent forced convection of coolant air flow (10 m/s velocity) in a steel tube of 50 cm long having outside diameter of 60 mm and inside diameter of 30 mm with constant outside surface temperature of 1000, 1200 and 1400 Ko is numerically analyzed. The renormalization group k-ε model is used to simulate turbulence in ANSYS - FLUENT 14.5. An opened ring of rectangular cross section (5x7 mm) is fitted in the tube and separated by 8cm pitch. Results of temperature and velocity distribution along the tube center line for the case of tube with internal ribs were compared with that of plain tube , these results show that the use of internal ribs enhance the heat transfer rate and found to possess the highest performance factors for turbulent flow.